Deletions in the 5' region of dystrophin and resulting phenotypes. Issue 11 (November 1994) - Muntoni, F; Gobbi, P; Sewry, C; Sherratt, T; Taylor, J; Sandhu, S K; Abbs, S; Roberts, R; Hodgson, S V; Bobrow, M
Abstract : Deletions in the dystrophin gene give rise to both Duchenne and Becker muscular dystrophies. Good correlation is generally found between the severity of the phenotype and the effect of the deletion on the reading frame: deletions that disrupt the reading frame result in a severe phenotype, while in frame deletions are associated with a milder disease course. Rare exceptions to this rule, mainly owing to frameshift mutations in the 5' region of the gene (in particular deletions involving exons 3 to 7) which are associated with a milder than expected phenotype, have been reported previously. In order to characterise better the relationship between genotype and phenotype as a result of mutations arising in the 5' region of the gene, we have studied a large cohort of patients with small in frame and out of frame deletions in the first 13 exons of the dystrophin gene. Fifty-five patients with a deletion in this area were identified; approximately one third of them had a phenotype different from that theoretically expected. Patients were divided into two groups: (1) patients with a severe clinical phenotype despite the presence of a small, in frame deletion and (2) patients with a mild phenotype and an out of frame deletion. Noticeable examples observed in the first group were Duchenne boys with a deletion of exon 5, of exon 3, and of exons 3-13. In the second group we observed several patients with an intermediate or Becker phenotype and out of frame deletions involving not only the usual exons 3-7 but also 5-7 and 3-6. These data indicate that a high proportion of patients with a deletion in the 5' end of the gene have a phenotype that is not predictable on the basis of the effect of the deletion on the reading frame. The N-terminus of dystrophin has at least one actin binding domain that might be affected by the small, in frame deletions in this area. The effect of the in frame deletions of exon 3, 5, and 3-13 on this domain might account for the severe phenotype observed in these patients. Other mechanisms, such as unexpected effect of the deletion on splicing behaviour, might, however, also be implicated in determining the phenotype outcome.